High Mortality During the Second Wave of the Coronavirus Disease 2019 (COVID-19) Pandemic in Uganda: Experience From a National Referral COVID-19 Treatment Unit. (18th November 2021) - Bongomin, Felix; Fleischer, Brian; Olum, Ronald; Natukunda, Barbra; Kiguli, Sarah; Byakika-Kibwika, Pauline; Baluku, Joseph Baruch; Nakwagala, Frederick Nelson
Abstract: Background: We evaluated clinical outcomes of patients hospitalized with coronavirus disease 2019 (COVID-19) in the second wave of the pandemic in a national COVID-19 treatment unit (CTU) in Uganda. Methods: We conducted a retrospective cohort study of COVID-19 patients hospitalized at the Mulago National Referral Hospital CTU between May 1 and July 11, 2021. We performed Kaplan-Meier analysis to evaluate all-cause in-hospital mortality. Results: Of the 477 participants, 247 (52%) were female, 15 (3%) had received at least 1 dose of the COVID-19 vaccine, and 223 (46%) had at least 1 comorbidity. The median age was 52 (interquartile range, 41–65) years. More than 80% of the patients presented with severe (19%, n=91) or critical (66%, n=315) COVID-19 illness. Overall, 174 (37%) patients died. Predictors of all-cause in-hospital mortality were as follows; age ≥50 years (adjusted odds ratio [aOR], 1.9; 95% confidence interval [CI], 1.2–3.2; P =.011), oxygen saturation at admission of ≥92% (aOR, 0.97; 95% CI, 0.91–0.95; P <.001), and admission pulse rate of ≥100 beats per minute (aOR, 1.01; 95% CI, 1.00–1.02; P =.042). The risk of death was 1.4-fold higher in female participants compared with their male counterparts (hazards ratio, 1.4; 95% CI, 1.0–2.0; P =.025). Conclusions: In this cohort, where the majority of the patients presented with severe or critical illness, more than one third of the patients hospitalized with COVID-19 at a national CTU died of the illness.